Lumberjanes. 13, Indoor recess - Watters, Shannon; Leyh, Kat; Stevenson, Noelle; Allen, Brooklyn; Ellis, Grace (Lumberjanes, 2019)
The woods outside of Miss Qiunzella Penniquiqul Thistle Crumpet's Camp for Hardcore Lady-Types are full of monsters, magic, and critters, and today it is storming outside. The Lumberjanes have just one job--stay indoors, dry, and stay out of trouble. However, confined to the mess room, Jo and Molly, Ripley, April, and Mal are sure to find trouble eventually--and they do. There is a secret tunnel beneath the kitchens complete with a gigantic, prehistoric bug.